Organic Design in Twentieth-Century Nordic Architecture - Champion, Erik (Routledge, 2019)
This book presents a communicable and useful definition of organic architecture that reaches beyond constraints. The book focuses on the works and writings of architects in Nordic countries, such as Sigurd Lewerentz, Jørn Utzon, Sverre Fehn and the Aaltos (Aino, Elissa and Alvar), among others. It is structured around the ideas of organic design principles that influenced them and allowed their work to evolve from one building to another. Erik Champion argues organic architecture can be viewed as a concerted attempt to thematically unify the built environment through the allegorical expression of ongoing interaction between designer, architectural brief and building-as-process.